The hypotheses in the research project: when yes, when no? - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
The use of hypotheses in the specialty finishing projects constitutes one of the methodological aspects that deserves an analysis. The article aims to clarify for young researchers when this category should be declared in a research. It is suggested to use the scope of the research (exploratory, descriptive, correlational or explanatory) for the decision of whether or not to use hypotheses in a research project. Conditions that determine the use of hypotheses specifically in descriptive studies, the most frequently carried out by residents are detailed.